The Relationship between Total Income and Groundwater Utilization on Fluviomarine Landform Area in Jakarta - Cahyadi Setiawan; S Suratman; Muh. Aris Marfai (Forum Geografi, 2017)
Approximately 40% of Jakarta is below sea level when the tide is in, which is referred to as a fluviomarine landform. This study aims: (a) to analyse the relationship between total income and household water demand, and (b) to analyse the relationship between total income and the proportion of groundwater utilization. It uses quantitative and qualitative analysis survey methods, as well as sampling methods, to represent the population. The population of this research is comprised of households that use groundwater on land units made from two classes of landform, two classes of settlement pattern, and three classes of settlement density. To determine the 30 wells, samples with proportional random sampling of the land units formed with groundwater samples have been taken at a radius of 100m from each well sample of 110 households. Quantitative and qualitative approaches have been used to prove the research aims. The analysis of this study indicates that the total income is proportional to household water demand but that it is inversely proportional to the share of groundwater utilization. The results also show that groundwater is not the only source to fulfil household water demand, and that it is necessary to utilize other sources of water.